2011
DOI: 10.1371/journal.pone.0023372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Decitabine in the Myelodysplastic Syndrome

Abstract: PurposeThe DNA methylation inhibitor 5-aza-2′-deoxycytidine (DAC) is approved for the treatment of myelodysplastic syndromes (MDS), but resistance to DAC develops during treatment and mechanisms of resistance remain unknown. Therefore, we investigated mechanisms of primary and secondary resistance to DAC in MDS.Patients and MethodsWe performed Quantitative Real-Time PCR to examine expression of genes related to DAC metabolism prior to therapy in 32 responders and non-responders with MDS as well as 14 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 27 publications
4
112
0
1
Order By: Relevance
“…Loss of DCK function is reported to be one of the mechanisms of decitabine resistance (Qin et al. 2009, 2011). Unexpectedly, the expression levels of DCK in the azacitidine‐resistant cells in the present study were not changed, although those azacitidine‐resistant cells showed strong cross‐resistance to decitabine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of DCK function is reported to be one of the mechanisms of decitabine resistance (Qin et al. 2009, 2011). Unexpectedly, the expression levels of DCK in the azacitidine‐resistant cells in the present study were not changed, although those azacitidine‐resistant cells showed strong cross‐resistance to decitabine.…”
Section: Discussionmentioning
confidence: 99%
“…2014) and deoxycytidine kinase (DCK) (Qin et al. 2009, 2011) are responsible for the resistance of azacitidine and decitabine, respectively, as the UCKs and the DCK are required for the HMAs to form their phosphorylated active metabolites. These metabolic changes observed in HMA resistance may have an impact on the efficacies of other antimetabolic agents, such as cytarabine, for the treatment of AML, that is, a possible risk of cross‐resistance in the treatment of MDS and/or AML.…”
Section: Introductionmentioning
confidence: 99%
“…Other FDA approved treatments, namely DAC and AZA, have been used in low-intensity MDS therapeutic regimens. However, due to untargeted DNA damage and mutagenesis, and the occurrence of primary and secondary resistance, DAC and AZA have demonstrated limited clinical responses (12,15). The future of MDS-targeted therapies may therefore require combinations of novel drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate at relapse following an initial response to treatment is poor. One study identified that primary resistance to treatment resulted from the abnormal active metabolism of DAC, and that secondary resistance was due to the unbalanced activation of downstream pathways, such as the nuclear factor-κB (NF-κB) and phosphatidylinositol 3-phosphate/AKT pathways, which limited the clinical effect of DAC (15).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical response to hypomethylating drugs in vivo is complex and may involve differentiation and immune activating components. Cytogenetic analysis showed that MDS patients after relapse using decitabine showed evolution in 20% patients with abnormalities such -7, del(16q) and +8 (Qin et al, 2011).…”
Section: Methylation Changes In Myelodysplastic Syndrome: Diagnosticmentioning
confidence: 99%